IMPLEMENTASI DAN PERMASALAHAN ASESMEN FORMATIF DALAM KURIKULUM MERDEKA PADA PEMBELAJARAN TEKS CERAMAH DI SMA MUHAMMADIYAH 10 SURABAYA - Faisal, Rakmat; Subandiah, Heni; Fanani, Zaenal (Hasta Wiyata, 2024)
The selection of assessment forms is essentially influenced by the applicable curriculum, the characteristics and subjects taught, which encourages the possibility of using more diverse and complex assessment models, techniques, and instruments. However, in practice, only a few assessment models, techniques, and instruments are used, which certainly impacts the validity and reliability of the assessment results. This research is basically conducted to analyze the implementation of formative assessment in assessing speaking skills in lecture text learning. This is important to be done in order to understand the results and problems that arise during its implementation. The research method used in this study is qualitative, using data collection techniques such as observation, interviews, and documentation, with the research location being at Muhammadiyah 10 High School in Surabaya